Իրանահայերի հայրենադարձութիւնը - Յակոբեան, Աստղիկ (տպ. Atlas)
The Victory of the Soviet Union in WWII ushered in the chance of massive repatriation of Armenians living abroad. Between May and November 25, 1946, 3870 families (20,597 individuals) repatriated to Soviet Armenia. Repatriation stopped for the next three years. The number of repatriated Iranian Armenians constituted a significant percentage of the total of 89,637 Armenians repatriated from abroad between 1946 and 1949. Repatriation from Iran continued in later years with certain interruptions. Between 1953 and 1959 some three to four thousand Armenians repatriated from different countries to Soviet Armenia. The mediation of the Soviet Armenian Communist Party and Soviet Armenian state authorities led to the Central Committee of the Communist Party of the Soviet Union and the Soviet government adopting a decision on August 12, 1961 for a massive new repatriation. Between 1962 and 1982, 31,920 Armenians (6795 families) were repatriated from 30 countries, including 24,283 (5039 families) Iranian Armenians. Once more, the Iranian Armenians constituted a significant proportion of the total repatriated Armenians. The paper focuses on the repatriation of the Iranian Armenians to Soviet Armenia, their points of departure from Iran, the villages and towns they vacated, the policies adopted by the Iranian authorities regarding repatriation and the settlement and integration of the Iranian Armenians in Soviet Armenian society and life.
Keywords: Պատմութիւն; Հայրենադարձութիւն